(untitled) (Environment & Health, 2020)
The derivatives of aromatic amino spirits are a promising group of the substances with antimycotic effect. Objective: The aim of the study was to investigate the sensitivity of clinical isolates of yeast-like fungi of Candida genus, obtained from oral subbiotopes of the patients with type I diabetes, to synthetic aromacyclic amino spirits and commercial antimycotics. Materials and methods: We applied the bibliosemantic, microscopic, mycological, statistical and analytical methods in the study. Results and discussion: 90 isolates of the representatives of Candida genus were isolated. The frequency of the isolation of yeast fungi in the oral biotope made up 66.1%. The level of oral candidiasis among patients with type I diabetes was 5.1%. C.albicans, C. glabrata, C. krusei, C. tropicalis, С. kefyr were indicated in the subbiotopes of oral cavity among the representatives of Candida genus, C. Albicans takes 67.8% , C. Glabrata - 10.0% , 16 , C. Krusei - 7% -, C. Tropicalis – 3.3%, S. kefyr - 2,2%. Among the compounds, Kc22 had the highest activity, which, at the concentration of 0.24-0.97 µg / ml, inhibited 59.0% of the strains. Amphotericin B showed the highest activity among commercial antimycotics. Fluconazole and intraconazole were ineffective against clinical strains. Conclusions: The frequency of the isolation of yeast fungi in the oral biotope in the patients with type I diabetes made up 66.2%. C. albicans is a predominant candid in all studied oral subbiotopes (67.8%). Clinical isolates are resistant to itraconazole (100%) and fluconazole (81.7%). All isolates were sensitive to amphotericin B (75.3%). Alkyl (aryloxyethoxy) dialkyl-aminopropanol derivatives had high anticandidous activity against all types of clinical isolates.